2006
DOI: 10.1016/j.ejcts.2005.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Platelet–monocyte pro-coagulant interactions in on-pump coronary surgery

Abstract: A higher postoperative platelet count as well as monocyte% significantly and independently decreases postoperative blood loss following cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…16,17 The lack of significant differences in circulating levels of TNF-α and IL-6 seems to exclude a downmodulating effect on the systemic inflammatory reaction exerted by the Synergy system when compared with standard CPB. Also, this observation can be confirmed by flow cytometric quantitative analysis of leukocyte activation antigens, which expression is modulated by the opposite effects of pro-and anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…16,17 The lack of significant differences in circulating levels of TNF-α and IL-6 seems to exclude a downmodulating effect on the systemic inflammatory reaction exerted by the Synergy system when compared with standard CPB. Also, this observation can be confirmed by flow cytometric quantitative analysis of leukocyte activation antigens, which expression is modulated by the opposite effects of pro-and anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the higher monocyte-platelet functional interaction, found in our study with standard CPB when compared with Synergy system, together with the recent demonstration that stable plateletmonocyte conjugates induce monocyte tissue factor (TF) expression, could explain the activation of the coagulation system, also via the extrinsic pathway, initiated with the binding of plasma factor VII (FVII) to TF on cell membranes. 16,17 The lack of significant differences in circulating levels of TNF-α and IL-6 seems to exclude a downmodulating effect on the systemic inflammatory reaction exerted by the Synergy system when compared with standard CPB. Also, this observation can be confirmed by flow cytometric quantitative analysis of leukocyte activation antigens, which expression is modulated by the opposite effects of pro-and anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research also observed this phenomenon and argued that this process is indicative of a persistent platelet activation and aggregation in the first three postoperative days. [16,22,23] In the present study, the platelet count delayed to show the rising tendency in the conventional group because those patients experienced a larger quantity of blood loss from the chest tube in the first 3 preoperative days. There were 69.2% of patients in the ABO group and 82.6% in the conventional group (P = 0.003) whose last re-examination of platelet count during in hospital stay was higher than the preoperative level (platelet rebound).…”
Section: Coagulation System Risk Factorsmentioning
confidence: 46%
“…The trajectory of platelet count is shown in Figure 3D and its pattern is similar to previous researches. [16,22,23] During CPB, the platelets were severely diluted and damaged and about 80% of patients required platelet transfusion to control bleeding from the suturing properly. Even with the plasma and platelet transfusion, the bleeding from the chest tube was still relatively large in the earlier postoperative days [Table and Supplementary Figure 1].…”
Section: Coagulation System Risk Factorsmentioning
confidence: 99%
“…TM is expressed constitutively on the surfaces of resting monocytes and macrophages [ 27 ]. Recently, we showed that domain 5 of TM co-localized with the cytoskeleton, F-actin, and intersectin I when the monocytes were stimulated by IL-6 [ 16 ], which is associated with cell migration and inflammatory responses [ 28 , 29 , 30 ]. TM concomitantly exhibits procoagulant activity and adhesion molecules expressing microparticles [ 31 ], which may be a key regulator of monocyte-related coagulation reactions.…”
Section: Discussionmentioning
confidence: 99%